Effect of flip angle on the accuracy and repeatability of hepatic proton density fat fraction estimation by complex data‐based, T1‐independent, T2*‐corrected, spectrum‐modeled MRI. Issue 2 (17th April 2013) - Johnson, Benjamin L.; Schroeder, Michael E.; Wolfson, Tanya; Gamst, Anthony C.; Hamilton, Gavin; Shiehmorteza, Masoud; Loomba, Rohit; Schwimmer, Jeffrey B.; Reeder, Scott; Middleton, Michael S.; Sirlin, Claude B.
<x xml:space="preserve">Abstract</x> Purpose To evaluate the effect of flip angle (FA) on accuracy and within‐examination repeatability of hepatic proton‐density fat fraction (PDFF) estimation with complex data‐based magnetic resonance imaging (MRI). Materials and Methods PDFF was estimated at 3T in 30 subjects using two sets of five MRI sequences with FA from 1° to 5° in each set. One set used 7 msec repetition time and acquired 6 echoes (TR7/E6); the other used 14 msec and acquired 12 echoes (TR14/E12). For each FA in both sets the accuracy of MRI‐PDFF was assessed relative to MR spectroscopy (MRS)‐PDFF using four regression parameters (slope, intercept, average bias, R2). Each subject had four random sequences repeated; within‐examination repeatability of MRI‐PDFF for each FA was assessed with intraclass correlation coefficient (ICC). Pairwise comparisons were made using bootstrap‐based tests. Results Most FAs provided high MRI‐PDFF estimation accuracy (intercept range −1.25 to 0.84, slope 0.89–1.06, average bias 0.24–1.65, R2 0.85–0.97). Most comparisons of regression parameters between FAs were not significant. Informally, in the TR7/E6 set, FAs of 2° and 3° provided the highest accuracy, while FAs of 1° and 5° provided the lowest. In the TR14/E12 set, accuracy parameters did not differ consistently between FAs. FAs in both sets provided high within‐examination repeatability (ICC range 0.981–0.998). Conclusion MRI‐PDFF was repeatable and, for most FAs, accurate in both sequence sets. In the TR7/E6 sequence set, FAs of 2° and 3° informally provided the highest accuracy. In the TR14/E12 sequence set, all FAs provided similar accuracy. J. Magn. Reson. Imaging 2014;39:440–447. © 2013 Wiley Periodicals, Inc.